The early modern Italian domestic interior, 1400-1700 : objects, spaces, domesticities - Campbell, Erin J.; Miller, Stephanie R.; Carroll, Elizabeth A. (Visual culture in early modernity, 2013)
Adopting a broad chronological framework and expanding the regional scope beyond Florence and Venice to include domestic interiors from less studied centers such as Urbino, Ferrara, and Bologna, this collection offers new perspectives on the home in early modern Italy. The volume's dual emphasis is on reconstructing the material culture of specific residences, and on how particular domestic objects reflect, shape, and mediate family values and relationships within the home.
Keywords: Interior decoration : Italy; House furnishings : Italy; Domestic space : Italy